Effects of Sources of Protein on Productive Performance and Immune Response in Commercial Broiler (Global Journal of Science Frontier Research, 2018)
The study was conducted to investigate the effect of different protein supplemented feed (animal protein, plant protein and combination of animal protein and plant protein) on the growth performance of broiler and the immune response of the birds against Newcastle Disease (ND). A total of 99 broiler birds were divided into 3 groups, each group consist of 33 individuals. Rations supplemented with animal protein, plant protein and combination of animal protein and plant protein were formulated for 3 treatment groups. Newcastle Disease vaccine was administered according to the vaccination schedule. Growth performance was measured using Feed Conversion Ratio (FCR) and immune response against ND using Haemaglutination Inhibition (HI) test. There was significant difference in growth performance due to variation in protein source of the supplied ration FCR was found 2.06, 1.64 and 1.68 for group A, B and C respectively. Antibody titre of the birds against ND vaccine virus was highest at day 7 is 7.10 and at day 28 is 6.90 in group-A birds supplemented with animal protein. The finding shows that immune response in broilers against ND depends on the protein source of the ration and animal protein is the best to have strong immunity.
Keywords: ration; protein source; growth performance; immune response